Nitric oxide synthase Glu298Asp gene polymorphism in cardiovascular diseases - Ibrahim, Wisam Nabeel; A.Talib, Norlelawati; Abdullah, Nor Zamzila (2014)

(untitled)
Ischemic heart disease (IHD), the leading cause of death worldwide, is a multifactorial disease arising from the complex interplay of genetic and environmental factors. There is considerable evidence that nitric oxide (NO) plays an important role in protecting against atherosclerosis, the process underlying IHD ( Spence et al., 2004). Endothelial-derived nitric oxide (NO) is synthesized by nitric oxide synthase (NOS). Variations in the human NOS gene have been identified. A single base nucleotide exchange polymorphism within exon 7 (G to T transition) at position 894 results in an exchange of glutamate (Glu) for an aspartate (Asp) amino acid, respectively, at position 298 in the enzyme (Hingorani ,1998). NOS Asp298 is subjected to selective proteolytic cleavage in endothelial cells and vascular tissues that might account for reduced vascular NO generation (Akhter, Biswas, & Saxena, 2009). Decreased NO and oxidative excess may activate matrix metalloproteinase (MMP) which weaken the fibrous cap. Because NO inhibits platelet aggregation, reduced NO contributes to thrombogenicity. Thus, endothelial dysfunction with reduced NO bioavailability, increased oxidant excess, and expression of adhesion molecules contributes not only to initiation but also to progression of atherosclerotic plaque formation and triggering of cardiovascular events such as ischemic heart disease(Uemura,2001).